PENGARUH PENAMBAHAN ETANOL DAN LAMA FERMENTASI LANJUTAN CAIRAN PULPA HASIL SAMPING FERMENTASI BIJI KAKAO TERHADAP KARAKTERISTIK CUKA KAKAO - Gora Adrista, Gede; Wartini, Ni Made; Arnata, I Wayan (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 4 No 4 (2016): Desember, 2017)
This study  aimed to  (1) determine the effect of ethanol addition and the fermentation period of pulp liquid by product  of cocoa beans  fermentation  to the characteristics of the  cocoa vinegar, and (2) determine the addition of ethanol  and  fermentation  period  to produce the characteristic cocoa vinegar of  pulp  liquid  by  product of fermentation best cocoa  beans. The experiments in this study using a  Split Plots design by treatment with the addition of ethanol into the main plot consisted of three plots namely 0%, 2,5% and 5% (v / v). Treatment of fermentation  period  is a sub  plot that consists of 6 levels namely  0, 2, 4, 6, 8, 10 days.  Pulp  liquid  fermentation  period which by product  of cocoa beans fermentation affect the levels of acetic acid, pH, and total dissolved solids of cocoa vinegar, meanwhile the interaction,  period  of fermentation  and the addition of alcohol  in  pulp  liquid  byproduct of fermentation of cocoa beans affect the degree of acidity (pH) of  cocoa  vinegar. Characteristics of  the best  cocoa vinegar  determined  by treatment  them  with the addition of etanol  by 5% and fermentation period  for 10 days with high levels of acetic acid, pH, total dissolved solids, alcohol  consistency, and total reducing sugar in a row was 2,86 (% w/w) , 3,67%, 5,25% brix, 0%, and 2,47%. Keywords: cocoa vinegar, cocoa, fermentation period, the addition of ethanol
Keywords: 115